Bone regeneration in critical-size calvarial defect using functional biocompatible osteoinductive herbal scaffolds and human umbilical cord Wharton's Jelly-derived mesenchymal stem cells. (March 2021) - Kashte, Shivaji; Dhumal, Rohit; Chaudhary, Pradip; Sharma, R.K.; Dighe, Vikas; Kadam, Sachin
Graphical abstract: Highlights: The scaffolds were prepared by layer by layer method as PCL, PCL-GO and PCL-GO-CQ. All the scaffolds were biocompatible. Post 12 week of transplantation of PCL-GO-CQ-hUCMSCs scaffolds showed nearly complete healing of critical size calvarial bone defect. A synergistic effect of GO and CQ helped hUCMSCs proliferation and differentiation into osteoblasts required for bone healing. PCL-GO-CQ-hUCMSCs scaffolds could pave the way for clinical trials and a potential alternative to bone grafts. Abstract: Critical size calvarial bone defects and their repair is the major challenge in orthopaedic surgery. Bone tissue engineering using varied combinations of scaffolds, stem cells, and growth factors is an emerging choice of treatment for variety of bone defects. Present study aimed to compare and evaluate the potential of poly ε-caprolactone (PCL), PCL- graphene oxide (GO), PCL-GO- Cissus quadrangularis (CQ), and human umbilical cord-derived mesenchymal stem cells (hUCMSCs) seeded PCL (PCL- hUCMSCs), PCL-GO-CQ-hUCMSCs scaffolds to heal critical size calvarial bone defect in the rat models. Healthy adult Wister female rats (N = 30) with average body weight of 350 ± 30 g were divided to 6 groups with five animals in each group. Single critical size calvarial defects of 8 mm were created in the skull of each rat and same were treated with respective scaffolds. The outcome of the treatments was evaluated at 6 weeks and 12 weeks in terms of weight, haematological parameters and biochemical parameters for biocompatibility. New bone regeneration/healing was analysed using digital radiography and micro-computed tomography. Quality of bone formed was analysed by bone mineral density. Histological analysis of the bone tissues was performed using an optical microscope. All the scaffolds were biocompatible and there was no adverse effect of these scaffolds on animals. Higher bone regeneration was observed after 12 weeks of transplantation than 6 weeks. However, PCL-GO-CQ-hUCMSCs scaffolds exhibited highest bone regeneration 12 weeks post-transplantation. The unique combination of PCL-GO-CQ-hUCMSCs scaffold proved to be beneficial in bone regeneration by aiding nearly complete healing of defect site. Further studies with PCL-GO-CQ-hUCMSCs could pave the way for human clinical trials.